2021
DOI: 10.2147/copd.s311772
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Caregiving Burden on Quality of Life of Caregivers of COPD Patients: The Chain Mediating Role of Social Support and Negative Coping Styles

Abstract: Purpose: Caregivers of COPD patients experience various caregiving burden, which is related to their quality of life. We aimed to explicitly explore whether social support and negative coping styles play the chain mediating roles in the relationship between the caregiving burden of caregivers of COPD patients and their health-related quality of life. Methods: We conducted a multicenter cross-sectional survey in four hospitals using a convenience sample. Participants who met the inclusion criteria completed fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“… 8 An increased caregiver burden has an immediate negative effect on the quality of life. 5 Next of kin of those with advanced COPD has a higher subjective caregiver burden than those of persons with COPD in earlier stages. 9 The next of kin needs strategies to support the affected person which develops over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 An increased caregiver burden has an immediate negative effect on the quality of life. 5 Next of kin of those with advanced COPD has a higher subjective caregiver burden than those of persons with COPD in earlier stages. 9 The next of kin needs strategies to support the affected person which develops over time.…”
Section: Introductionmentioning
confidence: 99%
“…When there is an imbalance between the stressors and possibilities to cope with the situation, caregiver burden emerges. 4 Negative coping styles lead to a higher caregiver burden 5 Caregiver burden includes aspects of emotional, social, physical, spiritual, and financial functions. 6 Thus, the caregiver burden is multidimensional 7 and the experiences are individual.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, more than a third of the caregivers reported that caring for their sick loved one was a high burden (ZBI score >24 points). Nevertheless, the mean ZBI score of 21.6±15.1 points was relatively low compared to a recent study reporting a mean ZBI score of 52.4±14.6 points in 201 caregivers of hospitalised patients with COPD [ 39 ]. However, since patients with COPD were hospitalised, we can assume that they had more severe disease compared to the patients in the present study, which could explain the higher caregiver burden score.…”
Section: Discussionmentioning
confidence: 59%
“…However, since patients with COPD were hospitalised, we can assume that they had more severe disease compared to the patients in the present study, which could explain the higher caregiver burden score. Moreover, in the study by Y i et al [ 39 ], caregivers were mostly the patients’ children (66%). It could be more difficult for the spouse (87% in the present study) to admit that their husband/wife is a burden.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increasing physical, mental, and financial pressures due to COPD exacerbation make FCs ignore their health and self-care and reduce their QOL. A study indicated that the FCs of patients with COPD had heavy CB and low QOL [ 11 ].…”
Section: Introductionmentioning
confidence: 99%